Penggunaan Palm Oil Mill Effluent (POME) dan Tepung Tapioka Sebagai Perekat Terhadap Karakteristik Briket Dari Limbah Padat Pabrik Kelapa Sawit - Aprizal, Aprizal; Fathoni, Ahmad; Armadani, Armadani (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid growth in demand for palm oil throughout the world has triggered the development of plantations which has an impact on the accumulation of palm oil waste. The resulting waste consists of empty oil palm fruit bunches, palm kernel shells, fiber, stems and fronds which have significant calorific value. This research aims to utilize liquid and solid waste produced from palm oil processing, especially liquid waste which is currently minimally utilized. One solution to this problem is briquette making to evaluate the characteristics of briquettes produced from a combination of shells, empty fruit bunches, solid decanters and liquid palm oil mill waste. The method applied in this research is an experiment that begins with literature study, survey, briquette making, testing, and data analysis. The test results showed that the highest heating value in sample A2 was 25137.95 cal/gram, the highest water content was in A2 with a value of 7.1%, the highest combustion rate was recorded in A1 at 0.16%, the highest ash content was obtained from A2 with a value of 14.4%, and the highest density was in A2B3 at 0.58%.